2023
DOI: 10.3390/jrfm16030156
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on the Information Content of Earnings Announcements for the Swiss Market

Abstract: A semi-strong efficient market incorporates relevant new information immediately. Using an event study, we investigate whether and to what extent regular earnings announcements of Swiss companies listed on the Swiss Market Index show the expected effects in share prices. For this purpose, we test for abnormal returns caused by earnings announcements in the period from 2012 until 2022. In contrast to previous studies of the Swiss market, we find that deviations from analysts’ expected earnings lead to pronounce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…where t is the year, and binned from −5 to 5 Beaver et al (1979), Kothari (2001), Bradshaw et al (2012), Kim (2018) We used a dependent variable as the abnormal returns by subtracting the average stock price change rate of the sector to which each company belonged from the individual company's stock price change rate (Sohn and Lee 2005;Chordia et al 2005;Kim 2018;Gregoire and Martineau 2022;Bänziger et al 2023). Thus, abnormal returns were denoted by…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where t is the year, and binned from −5 to 5 Beaver et al (1979), Kothari (2001), Bradshaw et al (2012), Kim (2018) We used a dependent variable as the abnormal returns by subtracting the average stock price change rate of the sector to which each company belonged from the individual company's stock price change rate (Sohn and Lee 2005;Chordia et al 2005;Kim 2018;Gregoire and Martineau 2022;Bänziger et al 2023). Thus, abnormal returns were denoted by…”
Section: Methodsmentioning
confidence: 99%
“…They found that the price response was insignificantly different from zero for each of the event days examined. Bänziger et al (2023) found a semi-strong efficient market between earnings announcements of Swiss companies and stock prices, and suggested that pre-and postannouncement abnormal returns were modest and generally not statistically significant. Fink (2021) also found that an earnings surprise did not lead to a full, instantaneous stock price adjustment, but rather to a low, predictable drift.…”
Section: Earnings Reports and Stock Pricesmentioning
confidence: 99%